2018
DOI: 10.25179/tjem.2017-59385
|View full text |Cite
|
Sign up to set email alerts
|

Work Patterns of Mothers Influence the Weights of Their Children

Abstract: Objective: Recent studies have reported a positive association between paid work hours of mothers and obesity in their children. Like most of other hospitals, nurses at our center work either on irregular shifts or on a regular basis. The aim of this study was to analyze factors affecting the weights of the children of female nurses. Material and Methods: We evaluated 100 children of female nurses on duty at our hospital. We prepared a questionnaire including details such as the gender of the child, birth-weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The study also reported that more children that were cared for by babysitters were underweight than those cared for by others. Babysitters may not provide the child with the appropriate nutritional support needed (Mousa 2018).…”
Section: Underweight Children Below Five Years: a Case Controlmentioning
confidence: 99%
“…The study also reported that more children that were cared for by babysitters were underweight than those cared for by others. Babysitters may not provide the child with the appropriate nutritional support needed (Mousa 2018).…”
Section: Underweight Children Below Five Years: a Case Controlmentioning
confidence: 99%
“…Another study has concluded that birth weight is associated with socioeconomic conditions, maternal nutrition, weight gain during pregnancy and antenatal care (7). Furthermore, study in Turkey in 2018 found that working status of both parents and gender of baby were associated with birth weight (8). Study in Pakistan reported that wealth index also related with birth weight (9).…”
Section: Kata Kunci: Berat Badan Lahir Perkotaan Pedesaan Faktor Risikomentioning
confidence: 99%